Perilaku Penyimpangan Wartawan Tim Peliputan Berita (Studi Kasus Penyimpangan dalam Peliputan Berita di Stasiun Televisi Siaran) - Chendy Liana (Institut Agama Islam Negeri (IAIN) Curup, 2016)
This study focuses on the phenomenon about deviation behavior of news coverage team reporter. In doing their duties, reporters regulated and guided by the Code of Ethics in Journalism which insists journalist to be professional in carrying out their jobs and provide valuable news whichare objective, equilibrate, neutral, honest and based on facts. The purpose of this study isto determine the forms, methods, and factors which cause behavioral aberrations byjournalist ofnews coverageteam consistsby Reporter and Cameraman in the